MOLECULAR DOCKING AND SCREENING OF DRUGS FOR 6LU7 PROTEASE INHIBITOR AS A POTENTIAL TARGET FOR COVID-19 - GADEWAR, MANOJ; LAL, BHARAT (International Journal of Applied Pharmaceutics, 2022)
Objective: The aim of present investigation is docking of various existing antiviral, anti-tubercular and anti-malarial drugs on 6LU7 receptor of SARS-CoV-2 in the treatment of COVID-19. Methods: In this study, the structure of coronavirus binding protein and ligands for various drugs were collected from the protein data bank and pub chem. Molecular docking was carried out using Schrodinger 9.0 software. In molecular docking study, 19 different drugs of various categories like antiviral, anti-malarial and anti-tubercular were investigated for analyzing binding to 6LU7 receptors of COVID-19. Results: The docking result showed a high affinity of zanamivir, montelukast, ramdesvir, ritonavir, cobicistat and favipravir to the 6LU7 receptor of novel coronavirus. Thus the combination of these drugs may be useful in preventing further infection and can be used as a potential target for further in vitro and in vivo studies of SARS-CoV-2. Conclusion: Treatment of COVID-19 has been challenge due to the non-availability of effective drug therapy. In this study, we reported drugs for targeting 6LU7 Mpro/3Clpro protein, which showed prominent effects as potential inhibitors of COVID-19 Mpro.